Monsters, Inc.: Curing Ethical Blindness in an Era of Test‐Based Accountability. Issue 2 (12th October 2020) - Slomp, David; Broad, Bob
Abstract: Discussions about literacy assessment can often be polarizing for teachers, school administrators, and other stakeholders. Given the diverse and often charged perspectives on assessment within both the profession and the broader public discourse, it can be difficult to engage in productive dialogue about the role that literacy assessment plays in promoting or inhibiting effective models of literacy education. This article provides perspectives, questions, and research that enables readers to better advocate for themselves and their students as they develop their own assessment programs and respond to assessment programs that are imposed on them.